2017
DOI: 10.1017/s0033291717000885
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil and cognitive enhancement in schizophrenia and healthy volunteers: the effects of test battery in a randomised controlled trial

Abstract: As in earlier chronic schizophrenia studies, modafinil failed to produce changes in cognition in early psychosis as measured by MCCB. CANTAB proved more sensitive to the effects of modafinil in participants with early schizophrenia and in healthy volunteers. This confirms the importance of selecting the appropriate test battery in treatment studies of cognition in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 46 publications
(83 reference statements)
2
31
0
2
Order By: Relevance
“…Reviewing evidence reported subsequence to this review supports these findings [15]. Evidence reviews have concluded that improvement in cognitive functions induced by modafinil could have a beneficial effect on broader aspects of patients' lives, including functional outcomes, quality of life and wellbeing [14].…”
Section: Modafinil and Schizophreniasupporting
confidence: 59%
See 2 more Smart Citations
“…Reviewing evidence reported subsequence to this review supports these findings [15]. Evidence reviews have concluded that improvement in cognitive functions induced by modafinil could have a beneficial effect on broader aspects of patients' lives, including functional outcomes, quality of life and wellbeing [14].…”
Section: Modafinil and Schizophreniasupporting
confidence: 59%
“…Research has shown that modafinil can enhance cognitive function in schizophrenia [14] [15] and has potential to enhance real life functioning [16] and reduce negative symptoms [17]. This potential requires further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It improves memory [ 31 ], executive function [ 32 ], and increases alertness and response accuracy in healthy subjects [ 25 ]. Importantly, the cognitive enhancer effect of modafinil has also been reported in a number of different neurological conditions including schizophrenia [ 33 , 34 ] and attention deficit hyperactivity disorder [ 35 ]. Modafinil has also been shown to be effective when given as an adjunct to standard treatment for treating mood disorders [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that modafinil improves episodic memory in patients with schizophrenia. This agent has also been reported to selectively improve spatial working memory and emotional processing (e.g.…”
mentioning
confidence: 99%